Pengaruh Social Media Marketing Terhadap Minat Berkunjung Ke Destinasi Wisata Pemandian Air Soda Tarutung - Daniel Adi Putra Pangaribuan; Christian B. Alexander L. Tobing (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2026)
This study aims to determine whether social media marketing influences the intention to visit the tourist destination Tarutung Soda Water Baths. A quantitative research method was employed, utilizing hypothesis testing—specifically the partial test (t-test) and the coefficient of determination (R²)—with data processed using SPSS Version 25. The sample size was 100 respondents, determined using the Slovin formula. The study concludes that the social media marketing variable (X) has a positive and significant partial effect on the intention to visit (Y), as evidenced by a calculated t-value exceeding the t-table value (9.561 > 1.9844). Furthermore, the regression result of 0.695 indicates that social media marketing (X) positively and significantly influences the intention to visit (Y) and represents a strong contributing factor. Consequently, the R-squared value was found to be 48.3%, while the remaining 51.7% is attributed to other variables.